Critical assessment of the use of growth monitoring for identifying high risk children in primary health care programmes. Issue 6688 (17th June 1989) - Briend, A.; Bari, A.
Abstract : OBJECTIVE–To see whether change in weight was a more useful index than weight for age in assessing the risk of dying among malnourished children. DESIGN–Prospective cohort study. SETTING–Rural community in Bangladesh being served by international health organisation. PARTICIPANTS–1011 Children aged under 5, of whom 66 died. END POINT–Efficient screening method for identifying malnourished children at risk of dying. MEASUREMENTS AND MAIN RESULTS–Weight was measured every month. Weight for age and monthly change in weight averaged over one and three months were calculated. Sensitivity and specificity curves were used to compare the values of these two variables in identifying children with a high risk of dying. Weight for age was more sensitive than change in weight at all levels of specificity. Changes in weight, however, were independently related to the risk of dying even when intercurrent diseases and low weight for age were taken into account. CONCLUSIONS–For identifying children with a high risk of dying weight for age is a more efficient screening tool than a recent change in weight. Growth monitoring as currently recommended for primary health care programmes in developing countries does not seem to be the most effective approach in identifying children in need of urgent help.